(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2021)
The uniqueness of riparian forest and its variation in landscape, geomorphology, contours of the water ways and drainage flow is of great ecological importance, and provides benefits to aquatic, terrestrial habitats and the species that live there. This study addressed the rate of degradation of the riparian vegetation of Omo Biosphere Reserve. The objective of this study was to determine the level of changes in the forest along the riparian zone of Omo Biosphere Reserve in Nigeria, as a basis for effective planning and sustainable management of riparian vegetation. Both primary and secondary data sources were exploited in this study. The primary data included the satellite images acquired over the study area from 1986 to 2016; while the secondary data included topographical maps, administrative boundary and limits of the biosphere reserves acquired from various sources. The satellite images included Landsat images of 1986, 1996, 2006; and 2016 of the study area. Digital image processing was carried out on all the remote sensed imageries; to enhance features of interest and for easy interpretation. The satellite images were processed, using the Erdas Imagine version 2014. The maximum likelihood algorithm classifier was used in classifying the images using the trained pixels into Forest, Settlement, Waterbody, Grassland/Shrubland, Riparian and Cultivation class. The trends of land-cover change showed gradual reduction in forest features, with overall loss of 30.57% of the initial forest cover in the 30-year period; while built-up, cultivations and shrubland/woodland experienced gains with cultivated land having the highest gains. It is concluded that decrease in riparian vegetation is a result of expansion in cultivated land and built-up areas. This implies the need for adopting management plans such as public education in biodiversity conservation, routine maintenance and strict adherence to conservation rules.